EFFECT OF IRRIGATION METHODS AND NUTRIENT MANAGEMENT PRACTICES ON PRODUCTION AND ECONOMICS OF POTATO UNDER DIFFERENT PRECEDING CROP SEQUENCES IN CENTRAL INDIA - Singh, Shiv Pratap; Sadaworti, MJ; Sharma, SK; Singh, RK; Rawal, S; Kumar, Manoj; Sharma, Jagdev; Katare, S (Potato Journal, 2024)
A field experiment was conducted at ICAR-Central Potato Research Institute-RS, Gwalior, in split-plot design: 3 irrigation methods (main plots) and 5 fertilizer doses in various crop sequences (sub-plots), with four replications. Results revealed that the highest total tuber number (604 thousand/ha) was recorded with dhaincha - potato (75% RDF NPK) which was significantly higher than all other treatments except green gram - potato (75% RDF NPK). Drip irrigation resulted in highest total tuber yield (35.8 t/ha), significantly surpassing other methods. Dhaincha - potato (75% RDF NPK) combination yielded (37.5 t/ha) highest, significantly outperforming others except fallow - potato (50% RDF NPK/ha + 15 t FYM) sequence. Drip irrigation x fallow - potato (50% RDF NPK/ha + 15 t FYM) combination recorded the highest total tuber yield at 40.3 t/ha. Drip irrigation resulted in water-use efficiency of 137 kg/ha-mm and harvest index of 72%,  significantly surpassing other methods. Fallow – potato {FYM 7.5 t/ha + crop residue 7.5 t/ha + biofertilizers (Azotobacter and PSB)} sequence recorded highest harvest index 73%, significantly surpassing other treatments. Drip irrigation resulted in highest WUE (137 kg/ha-mm), significantly surpassing other methods.  Combination of drip irrigation x fallow – potato (FYM 7.5 t/ha + 50% RDF NPK) sequence recorded highest WUE (155 kg tuber/ha-mm), significantly outperforming other treatments. Dhaincha – potato (75% RDF NPK) sequence resulted in the highest nitrogen content (216 kg/ha), significantly surpassing others. Dhaincha - potato (75% RDF NPK) sequence significantly out performed in tuber nitrogen uptake (77 kg/ha) to other sequences.    Combination of drip irrigation x dhaincha - potato (75% RDF NPK) sequence recorded highest N uptake (83 kg/ha). Benefit : cost was highest with drip irrigation (3.1) among irrigation methods and it was highest with dhaincha - potato (75% RDF NPK) sequence (2.99) among crop sequences.